Inflammation and the Migration of Mesenchymal Stem Cell - Reza Maulana; Nur Wahyuniati; Imai Indra (Syiah Kuala University, 2015)
Mesenchymal stem cells are adult non-hematopoietic stem cells with multilineage proliferation and differentiation capabilities. This type of stem cell has the multipotent ability to differentiate into osteocytes, tenocytes, adipocytes, chondrocytes and bone marrow stromal cells. The migration mechanism of mesenchymal stem cell is not yet fully understood, but based on studies that have been done recently by the researchers worldwide shown that the inflammatory process plays an important role for mesenchymal stem cell migration. A number of chemokine that plays a role in the migration of mesenchymal stem cells such as MCP-1 (CCL2), CXCL8, RANTES (CCL5), LL-37, integrin β1, CD44 receptor, CCR2, CCR3, and tyrosine kinase receptors for the following growth factors: IGF -1, PDGF-bb, HGF and VEGF